Improving knowledge skills through the application of Liveworksheet-based modules on the Static Equilibrium of Rigid Bodies - Adinda Kiky Maulita Pratiwi; Suharno Suharno; Pujayanto (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2026)
This research aims to develop a e-module based on Liveworksheet about Static Equilibrium of Rigid Bodies that effectively improves students' knowledge skills. This study uses the R&D method with the ADDIE development model. The subjects were 30 students of class XI E of State Senior High School 7 Surakarta. The instruments used in this study included an e-module validation sheet and a pretest– posttest on knowledge skills. Data analysis techniques used descriptive and inferential statistical analysis through N-Gain and Paired Sample T-test. The results showed that the developed emodule was categorized as very good based on expert validation. The N-Gain analysis obtained a score of 0.40 in the moderate category. In addition, the results of the Paired Sample T-test showed a significant value of 0.000 <0.05, which indicated a significant difference between students' pretest and posttest scores after using the Liveworksheet-based e-module. The conclusion of this study is that the developed Liveworksheet-based e-module ia quite effective in improving students' knowledge skills on Static Equilibrium of Rigid Bodies.